Pengaruh Kepemimpinan dan Komitmen Organisasi Terhadap Kinerja Pegawai Pada Dinas Perdagangan dan Perindustrian Kabupaten Gowa - Ady Andardinata; Nurul Fadilah Aswar; Muhammad Ilham Alimuddin; Ryan Wahyudi Ramli (STIM-LPI Makassar, 2023)
This study aims to determine the effect of leadership and organizational commitment on employee performance at the Department of Trade and Industry of Gowa Regency. The types of data used in this study are qualitative data and quantitative data. The data analysis method used is descriptive analysis and statistical analysis which includes multiple linear regression analysis, correlation coefficient, determination coefficient, t test and F test. Gowa Regency Industry. Therefore, the hypothesis proposed in this study is accepted.